Relationship between Nonalcoholic Fatty Liver Disease and Vitamin D Nutritional Status in Extreme Obesity - Adryana Cordeiro; Silvia Pereira; Carlos José Saboya; Andrea Ramalho (Canadian Journal of Gastroenterology and Hepatology)
Aim. To evaluate the relationship of nonalcoholic fatty liver disease (NAFLD) with nutritional status of vitamin D in extreme obesity. Methods. Descriptive cross-sectional study in individuals with class III obesity (BMI ≥ 40 kg/m2), aged ≥ 20 years to < 60 years. Data were obtained for weight, height, waist circumference (WC), and serum 25-hydroxyvitamin D (25(OH)D) levels. Vitamin D analysis was performed by high performance liquid chromatography (HPLC) and the cutoff points used for its classification were < 20 ng/mL for deficiency and 20–29.9 ng/ml for insufficiency. NAFLD gradation was conducted through histological evaluation by liver biopsy. Results. The sample is comprised of 50 individuals (86% female). BMI and average weight were 44.1 ± 3.8 kg/m2 and 121.4 ± 21.4 kg, respectively. Sample distribution according to serum 25(OH)D levels showed 42% of deficiency and 48% of insufficiency. The diagnosis of NAFLD was confirmed in 100% of the individuals, of which 70% had steatosis and 30% had steatohepatitis. The highest percentage of 25(OH)D insufficiency was seen in individuals with steatosis (66%/n=21) and steatohepatitis (93%/n=16). All individuals with steatohepatitis presented VDD (p<0.01). Conclusion. The results of this study showed high prevalence of serum 25(OH)D inadequacy in individuals with class III obesity, which worsens as the stage of liver disease progresses.